Some oral microbiota in complete cleft infants in comparison with normal infants - Rula Qays Abdulkareem Al-Humairi; Zainab Juma Jafar (Journal of the Pakistan Medical Association)
Objective: To compare caries-related microorganisms and candida in complete cleft infants with normal palate infants.